Painted glories : the Brancacci Chapel in Renaissance Florence - Eckstein, Nicholas A. (Yale University Press, 2014)
In 1440, on the feast of Saints Peter and Paul, Florence unexpectedly defeated Milanese forces near the town of Anghiari in eastern Tuscany. Nicholas A. Eckstein reveals the impact of this celebrated victory on Florentine public life and how it could have triggered the custodians of the Brancacci Chapel, the Carmelite friars, to seek the completion of frescoes by Masolino (1383-1447) and Masaccio (1401-1428). Today, tens of thousands of people visit the Brancacci Chapel annually to gaze at the brilliant frescoes of Saint Peter's life. Universally recognized as a canonical masterpiece of the Florentine Renaissance, these glowing murals span the interior in long panels. The first serious examination to position the frescoes at the heart of Tuscan society and culture, Painted Glories teems with fascinating characters and intrigue. In swiftly paced prose, Eckstein explores the chapel's history, medieval culture, and art patronage, progressively peeling back the story's layers amid the tumultuous politics of the 15th-century Florentine state.
Keywords: Cappella Brancacci (Santa Maria del Carmine (Church : Florence, Italy)); Carmelites : Art patronage : Italy : Florence; 1400-luku; 1500-luku; Art and society : Italy : Florence : History : To 1500; Christian art and symbolism : Italy : Florence : Medieval, 500-1500; Mural painting and decoration, Italian : Italy : Florence; Mural painting and decoration, Renaissance : Italy : Florence; kappelit; koristelu; seinämaalaukset; Firenze